SARS-CoV-2 Viral Load Is Correlated With the Disease Severity and Mortality in Patients With Cancer - Al-Mozaini, Maha; Noman, Abu Shadat M.; Alotaibi, Jawaher; Karim, Mohammed Rezaul; Zahed, A. S. M.; Karim, A. T. M. Rezaul; Alromiah, Khaldoun; Islam, Syed S. (Frontiers in Oncology, 2021)
Emerging evidence suggests that patients with cancer are at increased risk of detrimental Covid-19 outcome. The relationship between SARS-CoV-2 viral load and risk factors and outcome of SARS-CoV-2 positive cancer patients remains largely unexplored. We assessed the outcomes of Covid-19 infection in 64 cancer patients and 120 non-cancer and measured SARS-CoV-2 viral load from nasopharyngeal swab samples using cycle threshold (Ct) values who were admitted to two geographically distinct hospitals. We also assessed the incubation period and serial interval time differences between the non-cancer and cancer groups. Our results indicated that the overall mortality rate was higher among cancer patients with a high SARS-CoV-2 viral load. Covid-19 positive cancer patients with higher viral load are more prone to severe outcomes compared to non-cancer and low viral load patients. In addition, patients with lung and hematologic cancer have higher tendencies of severe events in proportion to high viral load. Higher attributable mortality and severity were directly proportional to high viral load particularly patients who are receiving anticancer treatment. Importantly, we found that the incubation period and serial interval time is fairly shorter in cancer patients compared with non-cancer cases. Our report suggests that high SARS-CoV-2 viral loads may play significant role in the overall mortality and severity of Covid-19 positive cancer patients and warranted further study to explore the disease pathogenesis and their use as prognostic tools.